The Werewolf of Bamberg - Pötzsch, Oliver (Pötzsch, Oliver. Hangman's daughter tale., 2015)
In 1668, hangman Jakob Kuisl, his daughter Magdalena, and her husband Simon travel to the town of Bamberg. But what was planned as a family vacation soon becomes a nightmare: a murderer in Bamberg is leaving the severed limbs of victims in the trash outside the city. When rumors quickly spread that the deaths are the work of a werewolf, Jakob must prove the superstition wrong and embarks on a search for the “devil of Bamberg.”